The Mediating Effect of Organizational Commitment on the Relationship between Job Stress and Employee Engagement (American Journal of Multidisciplinary Research and Innovation, 2025)
This study examined the mediating effect of organizational commitment on the relationship between job stress and employee engagement among public-school teachers in the Division of Davao Del Sur. Utilizing a descriptive-correlational research design, data were collected from teacher-respondents through validated instruments. The findings revealed very high levels of job stress, organizational commitment, and employee engagement among respondents. However, no significant relationships were found between job stress and employee engagement, job stress and organizational commitment, and organizational commitment and employee engagement. Additionally, organizational commitment showed no mediating effect on the relationship between job stress and employee engagement. These results suggest the need for further exploration of teacher well-being and its impact on organizational outcomes. The study contributes to the understanding of teacher dynamics in public schools and underscores the importance of theoretical frameworks like the Conservation of Resources (COR) Theory to provide insights into these complex relationships.